(2X平方-3X+1)平方-22X平方+33X-1
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 21:52:49
(2X平方-3X+1)平方-22X平方+33X-1(2X平方-3X+1)平方-22X平方+33X-1(2X平方-3X+1)平方-22X平方+33X-1原式=(2x²-3x+1)²-
(2X平方-3X+1)平方-22X平方+33X-1
(2X平方-3X+1)平方-22X平方+33X-1
(2X平方-3X+1)平方-22X平方+33X-1
原式=(2x²-3x+1)²-22x²+33x-11+10
=(2x²-3x+1)²-11(2x²-3x+1)+10
=(2x²-3x+1-1)(2x²-3x+1-10)
=(2x²-3x)(2x²-3x-9)
=x(2x-3)(x-3)(2x+3)
(2x²-3x+1)²-22x²+33x-1
=(2x²-3x+1)-11(2x²-3x+1)+11-1
=(2x²-3x-9)(2x²-3x)
=x(2x-3)(x-3)(2x+3)
(x平方-1)的平方-(2x+2)平方 (x平方+x)(x平方+x-2)-3(x平方-1)的平方-(2x+2)平方(x平方+x)(x平方+x-2)-3分解因式
(2X平方-3X+1)平方-22X平方+33X-1
因式分解(2x平方-3x+1)平方-22x平方+33-1
(2x+1)平方-x平方
(-2x平方+3x)-[5x-(2x平方+1)-x平方] 化简
(2x平方-3x+1)平方-22x平方+33x-1 (x+3)(x平方-1)(x+5)-20(x+y)三次方+2xy(1-x-y)-1(x平方+x+1)(x平方+x+2)-12(x平方+3x+2)(4x平方+8x+3)-90(x平方+4x+8)平方+3x(x平方+4x+8)+2x平方
(2x平方-3x+1)平方=22x平方-33x +1解方程
x平方-3[2x-5(x平方-x+1)]
(x平方-1)平方=9 (2X平方-3)平方=4
(3x-1)平方=(x+2)平方
(2x-1)平方-(2-3x)平方
x(x平方-1)+2X平方(X+1)-3X(2X-5)帮个忙
(2乘以X的平方-3X+1)的平方-22乘以X的平方+33X-1
x(x-1)-(x平方-y)=-3,求x平方+y平方-2xy完全平方公式
(1-x/3-x)平方除以x平方-6x+9/9-x平方*1/x平方-2x+1
x^4-x平方 a(x平方-y平方)+b(y平方-x平方) -27x^4+18x^3-3x平方 x^4-1
3/2x的平方-(-1/2x的平方)+(-2x的平方)
9X平方;+4=(3X平方-1)(2X平方+2)